Dynamic observation on collateral circulation construction of patient with vertebral artery restenosis after stenting: case report. (10th December 2021) - Yin, Yan-Wei; Sun, Qian-Qian; Chen, Da-Wei; Zhao, Fa-Guo; Shi, Jin
Abstract: Purpose/aim of the study: Posterior circulation stroke (PCS) accounts for 20% of ischemic stroke, and vertebrobasilar stenosis is an important cause of PCS. Notably, not all patients with artery stenosis progress to ischemic stroke, and one of the important reason is that collateral circulation construction plays important protection role in this process. Clinical presentation: Here, we present the case of a 71-year-old male who presented with lightheadedness and three episodes of loss of consciousness after bilateral subclavian artery stenting. Digital subtraction angiography (DSA) demonstrated severe stenosis of the left vertebral artery, and the bilateral subclavian artery was kept open. The patient was then given the left vertebral artery stenting in an effort to resolve the vascular stenosis. As expected, he achieved a complete remission after stenting. However, 6 months later the patient suffered from loss of consciousness again. Repeat DSA confirmed restenosis of the left vertebral artery, and revealed a collateral flow to the left vertebral artery which fed by external carotid collateral branches. Then DSA was performed after 12 months, and another collateral circulation involving thyrocervical trunk was also found supplying flow to the left vertebral artery. In this process, the frequency of loss of consciousness gradually decreased as the collateral circulation construction. Conclusion: Through this case, we observe the whole process of the collateral circulation construction. Moreover, this case serves as a testament to the variability and complexity of vertebrobasilar arteriopathies, suggesting promotion of collateral flow offers the opportunity for outcome improvement.